2022
DOI: 10.21203/rs.3.rs-1742763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LPAR5 confers cancer cells radioresistance associated with EMT activation via ERK/ Snail pathway

Abstract: Epithelial-to-mesenchymal transition (EMT) is a critical event contributing cancer cells more aggressive phenotypes. EMT programs are frequently activated in radiation-targeted cells during the course of radiotherapy, and which often endows cancers the acquired radioresistance. Through RNA-seq based transcriptome analysis, here we found that LPAR5 is downregulated in the early response of HeLa cells to γ-rays irradiation. Radiation-induced alterations of LPAR5 expression were further revealed to be a bidirecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Although a remarkablly increased M 6 A level in RNAs was induced in U2OS cells by UV irradiation, no induction of M 6 A was observed by 10 Gy of γ-ray IR [52]. Our team's latest research indicated that the overall M 6 A level of RNAs was decreased at 2 h and until 12 h after 4Gy γ-ray irradiation in both HeLa and HepG2 cells [57], that is due to the depressed expression of METTL3 by IR. Transcriptome-wide m 6 Aseq and RNA-seq assays also indicate that the ratio of manscripts with decreased M 6 A level is higher than that of increased level.…”
Section: Impacts Of Radiation On Rna M 6 a Methylationmentioning
confidence: 81%
“…Although a remarkablly increased M 6 A level in RNAs was induced in U2OS cells by UV irradiation, no induction of M 6 A was observed by 10 Gy of γ-ray IR [52]. Our team's latest research indicated that the overall M 6 A level of RNAs was decreased at 2 h and until 12 h after 4Gy γ-ray irradiation in both HeLa and HepG2 cells [57], that is due to the depressed expression of METTL3 by IR. Transcriptome-wide m 6 Aseq and RNA-seq assays also indicate that the ratio of manscripts with decreased M 6 A level is higher than that of increased level.…”
Section: Impacts Of Radiation On Rna M 6 a Methylationmentioning
confidence: 81%